The boundaries in the area of knowledge transfer in management consulting - Lopes da Costa, R.; António, N.; Sampaio. M.; Miguel, I. (Gestão e Produção, 2021)
In a historical retrospective, although the existing literature calls the management consulting industry an extraordinary sector and a unique phenomenon in the business context, in fact these statements are not accompanied by a number of academic studies that emphasize the importance of the effective work of the management consultants. To contest the lack of studies in this emerging area, this article aims to understand the implications of the border to the transfer of information and knowledge from management consultants to their client companies. The results of the empirical analysis in the form of semi-structured interviews and questionnaires applied to management consultants and SME managers in Portugal reveal that the competency factor must be based on the four knowledge families of business management - the know- know, the competence, know-how and know-how to be and it is only from this conjugation that any kind of constraints that can be found along the way (political, physical or cultural) are able to be unblocked.